Organic chemistry ([Singapore] : McGraw-Hill Education, 2016)
Designed to meet the needs of the "mainstream," two-semester, undergraduate organic chemistry course, this text gives students a solid understanding of organic chemistry by stressing how fundamental reaction mechanisms function and reactions occur.
1 Structure Determines Properties 2 Alkanes and Cycloalkanes: Introduction to Hydrocarbons 3 Alkanes and Cycloalkanes: Conformations and cis-trans Stereoisomers 4 Chirality 5 Alcohols and Alkyl Halides: Introduction to Reaction Mechanisms 6 Nucleophilic Substitution 7 Structure and Preparation of Alkenes: Elimination Reactions 8 Addition Reactions of Alkenes 9 Alkynes 10 Introduction to Free Radicals 11 Conjugation in Alkadienes and Allylic Systems 12 Arenes and Aromaticity 13 Electrophilic and Nucleophilic Aromatic Substitution 14 Spectroscopy 15 Organometallic Compounds 16 Alcohols, Diols, and Thiols 17 Ethers, Epoxides, and Sulfides 18 Aldehydes and Ketones: Nucleophilic Addition to the Carbonyl Group 19 Carboxylic Acids 20 Carboxylic Acid Derivatives: Nucleophilic Acyl Substitution 21 Enols and Enolates 22 Amines 23 Phenols 24 Carbohydrates 25 Lipids 26 Amino Acids, Peptides, and Proteins 27 Nucleosides, Nucleotides, and Nucleic Acids 28 Synthetic Polymers GLOSSARY CREDITS INDEX
"This international student edition is for use outside the U.S."--Cover.
Keywords: Chemistry, Organic; Chemistry, Organic - Problems, exercises